Fastställande av referensintervall för fibrinogen i plasma hos friska föl - Tholander, Maria (2004)
Fibrinogen concentrations were analysed in EDTA preserved blood plasma samples from 34 thoroughbred foals born in 2001 and 2002 at one stud farm. The foals were between 0 and 240 days old at the time of the sampling, and there were 19 fillies and 12 stallions in the group. The foals were examined for clinical symptoms of disease and their body temperature was measured before blood was sampled from the jugular vein. From totally 156 blood samples, 31 were selected as originating from clinically healthy foals, and used to determine a reference range for thoroughbred foals. Samples originating from foals showing clinical symptoms of disease or an abnormal body temperature at the time of sampling, were classified as coming from unhealthy animals.